CARBON DIOXIDE REMOVAL USING AMMONIA IN BIOGAS UPGRADING AND PURIFICATION - MAILE, Ireen O.; MUZENDA, E. (Studia Universitatis Babeș-Bolyai Chemia, 2017)
An alternative source of energy like biogas has become of interest to reduce the dependence on depleting fossil fuels for the source of energy. It is environmentally friendly and can be generated from various biomass wastes. It consists of CH4 (55%- 65%) and CO2 (35%- 45%) with a calorific value of 22 000- 25 000 kJ/m3 when raw and after CO2 is removed, the methane gas has a calorific value up to 39 000 kJ/ m3 and is referred to as biomethane. Ammonia is used as an absorbent in chemical scrubbing to remove CO2 from biogas. A continuous system consisting of 1L digester was used for biogas production which was bubbled through an absorbent in 500mL gas washing bottle at a constant temperature in a water bath. The obtained biomethane potential was found to be 0.387 m3 CH4/ kg VS which simply means that more methane gas can be obtained when using ammonia for absorption. An increase in the gas flow rate leads to an increase in the mass transfer coefficient resulting in an increase in the rate of absorption. The initial CO2 concentration affects the removal efficiency because more work needs to be done for biogas with a high initial concentration of CO2. NH3 has better absorption capacity because higher biogas purity was achieved at lower NH3 concentration. The removal efficiency for NH3 increased from 69%-79% on average with CH4 concentration reaching over 85% vol. This is equivalent to a calorific value ranging from 25- 33.5 MJ/Nm3 which is promising in terms of the gas ability to run in an automobile engine.